Implementasi Metode Saw Dan Wp Pada Sistem Pendukung Keputusan Penghuni Asrama Mahasiswa Papua Kota Palangka Raya - Sari, Nova Noor Kamala; Bamulki, Margareta (Journal of Information Technology and Computer Science, 2022)
The Papuan Student Dormitory is one of the dormitories located at Jalan B'Koetin No 92, Palangka Village, Jekan Raya District, Palangka Raya City 73112, and is a dormitory inhabited by students from Papua who are pursuing Bachelor's Degree Education by getting educational assistance called Adik Papua (Papua Affirmation) at the University of Palangka Raya. Students who receive the Papua ADik Affirmation Program at Palangka Raya University are placed in the Papuan Student Dormitory where there are 40 rooms in all. The hostel management and also the Chancellor are in charge of the Papua ADik Papua Program Recipient Students. There are 2 goals in creating this system, namely to build a website-based Papua Student Dormitory Selection System that can be used to determine students who are entitled and eligible to live in Papuan Student Dormitories and Make a Comparison of the Simple Additive Weighting (SAW) Method and the Weighted Product (WP) Method ) in ranking to find out the best method recommendations. the results of this test can also be compared with the two methods with the same value, so it can be concluded that the DSS based on this website with the two methods used are very relevant